Protecting women’s sports? Anti-trans youth sports bills and white supremacy - Fischer, Mia (Communication and critical/cultural studies, 2023)
An unprecedented number of anti-transgender youth sports bills have been introduced in various state legislatures across the United States since 2020. These bills seek to bar trans youth from playing and competing in sports that align with their gender identity. Scrutinizing the rise in these bills and the fearmongering that accompanies them, this article untangles how the deployment of a white feminist rhetoric of “protecting women’s sports” by a coalition of anti-LGBTQ Christian conservative forces and trans-exclusionary radical feminist (TERF) women’s sports advocates shields these bills and their proponents from accusations of transphobia and bigotry while obscuring their white supremacist underpinnings.